Look for the meaning of rural school work: Qualitative study on identity of comprehensive teachers in rural primary schools in China - Lian, Yang; Xiaojun, He; Cuiling, Wu (Frontiers in Psychology, 2023)
In the working environment of rural schools, whether and how does the identity of new comprehensive teachers change before and after service? Research on this problem is beneficial to optimize pre-service training and provide effective support for in-service training. In this study, phenomenological interviews were conducted to understand the formation and change of their identities in the three stages of pre-service, working and current teaching of four new teachers with three-year teaching experience in the minority areas of western China. The results show that in the working environment of rural schools, three comprehensive teachers in primary schools have gradually changed from being excellent subject teachers to caring teachers. Another determined to become a caring teacher before her career, she retained her own identity in her work and focused more on the healthy growth of her students. The results show that the working environment of rural schools has a significant impact on the identity of first-term teachers of primary schools. Pre-service training should be integrated into local culture to promote the integration of pre-service and in-service and realize its sustainable development.